2015
DOI: 10.1007/s00266-015-0524-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Level Laser Therapy on Human Adipose-Derived Stem Cells: In Vitro and In Vivo Studies

Abstract: This journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors http://www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Cell proliferation can be positively influenced by LLLT as already shown in various studies (Emelyanov & Kiryanova, ; Li, Chen, & Huang, ; Lipovsky, Oron, Gedanken, & Lubart, ; Min et al, ). This is in consistence with our findings of increased sizes of colonies in the CFU‐F assay.…”
Section: Discussionmentioning
confidence: 52%
“…Cell proliferation can be positively influenced by LLLT as already shown in various studies (Emelyanov & Kiryanova, ; Li, Chen, & Huang, ; Lipovsky, Oron, Gedanken, & Lubart, ; Min et al, ). This is in consistence with our findings of increased sizes of colonies in the CFU‐F assay.…”
Section: Discussionmentioning
confidence: 52%
“…Their in vivo results also revealed elevated numbers of stem cells compared to the control group [116]. Epidermal stem cells can also be influenced by light, as demonstrated by Liao et al The authors reveal that 632.8 nm light has photobiological effects on cultured human epidermal stem cells, such as an increase in proliferation and migration in vitro [110].…”
Section: Molecular Mechanisms Of Pbmmentioning
confidence: 99%
“…( 3 - 5 ) The only study assessing the effect of LLLI with wavelengths higher than 800nm on ADSC showed a 830nm laser (0.05J/cm 2 ) promoted an increase in cell proliferation of ADSCs compared to the Control Group. ( 7 )…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several studies have evaluated the effect of low-level laser irradiation (LLLI) on the proliferation of mesenchymal stem cells (MSC) obtained from different sources, ( 2 ) and satisfactory results were reported on ADSC. ( 3 - 7 ) Thus, laser therapy has emerged as an alternative to stimulate in vitro cell proliferation.…”
Section: Introductionmentioning
confidence: 99%